Effect of Nerve Mobilization in Reducing Pain in Patients with Guyon Canal Syndrome - Maliesgasari, Dita; Sudaryanto, Wahyu Tri (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Guyon Canal Syndrome is a peripheral ulnar neuropathy caused by lesions of the distal ulnar nerve, specifically in the Guyon's tunnel which is at the base of the hypothenar eminence where the ulnar nerve branches and is susceptible to compression. These tunnel structures are frequently subject to cycling-related injuries, sudden compression or repetitive vibration. Guyon Canal Syndrome causes loss of motor, sensory function, or a combination of motor and sensory function. The aim of this research is to determine the effect of nerve mobilization on reducing pain in Guyon Canal Syndrome. Subjects and Method: This research is a quasi-experimental research conducted at the Grhasia Mental Hospital, Yogyakarta Special Region, in June-July 2023. A total sample of 8 patients diagnosed with Guyon canal syndrome was selected using purposive sampling. The sample was divided into 2 groups (1) 4 people received nerve mobilization and (2) 4 people received standard care. The dependent variable is pain. The independent variable is nerve mobilization. Pain was measured using the Quadruple Visual Analogue Scale (QVAS). The difference in pain scores before and after intervention in the two groups was tested using an independent t test. Results: The average difference in pain score reduction in the intervention group (Mean= -11.75; SD= 5.68) was greater than the control (Mean= -3.5; SD= 11.39), but not statistically significant (p= 0.242). Conclusion: The average difference in pain score reduction in the intervention group was greater than the control, but not statistically significant. Keywords: Guyon canal syndrome, pain, nerve mobilization